2019
DOI: 10.14309/crj.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Persistent Cystic Duct Stump Leak Following Cholecystectomy With Percutaneous Transabdominal Cystic Duct Stump Embolization

Abstract: Cystic duct stump leak remains a difficult clinical problem despite advancements in endoscopic techniques. When these minimally invasive strategies fail, patients are often subject to high morbidity and mortality associated with open surgical exploration. We report the successful treatment of persistent biliary leak from the cystic duct stump following cholecystectomy using percutaneous transabdominal access of the cystic duct and coil embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Benefits of this procedure include the ability to define the source of the leak, remove any present stones, and sealing the leak. This is most commonly accomplished by means of endoscopic stenting and sphincterotomy or percutaneous transhepatic biliary drainage [ 13 ]. As a result, distal bile duct pressure is reduced, allowing for the closure of the site of the leak [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Benefits of this procedure include the ability to define the source of the leak, remove any present stones, and sealing the leak. This is most commonly accomplished by means of endoscopic stenting and sphincterotomy or percutaneous transhepatic biliary drainage [ 13 ]. As a result, distal bile duct pressure is reduced, allowing for the closure of the site of the leak [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Schelhammer et al 13 first described the successful embolization of a cystic duct stump after cholecystectomy. In addition, Brown et al 14 reported the successful treatment of a persistent biliary leak from the cystic duct stump after cholecystectomy using percutaneous transabdominal access of the cystic duct and coil embolization. Kirtane et al 15 reported the first successful intrahepatic coil embolization for persistent biliary leak after abdominal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Given the risks associated with persistent bile leaks and lack of consensus in therapeutic choices, innovative endoscopic modalities have been pursued, including the use of endovascular coils for biliary leak embolization. [9][10][11][12][13][14][15] We present a case of endoscopically placed metallic coils for embolization of a refractory bile leak after penetrating abdominal trauma.…”
Section: Introductionmentioning
confidence: 99%
“…2 Choledochoscopy has been previously used for large bile leaks in conjunction with percutaneous transhepatic approaches; however, similar success using ERCP alone is less common and more technically challenging. [3][4][5] Because glue solidifies instantly after leaving the catheter, it necessitates precise deployment on the first attempt. Direct visualization with choledochoscopy facilitates cannulation and ensures accurate deployment, avoiding the unnecessary exclusion of healthy parenchyma.…”
mentioning
confidence: 99%